2006
DOI: 10.1111/j.1744-7429.2006.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod Abundance, Canopy Structure, and Microclimate in a Bornean Lowland Tropical Rain Forest1

Abstract: This study applies a novel, vertically stratified fogging protocol to document arthropod abundance, density, and biomass across a vertical gradient in a primary, lowland dipterocarp forest canopy in Borneo. We fogged arthropods at 5 m vertical intervals and 20 m horizontal intervals along six full‐canopy transects and measured leaf surface areas along the same transects. The results show that arthropod biomass in the aboveground regions was 23.6 kg/ha, the abundance was 23.9 million individuals/ha, and the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 25 publications
3
91
1
Order By: Relevance
“…The integration of daily mean humidity is then transferred isotopically into the chitin (C 8 H 13 O 5 N), together with a systematic (and constant) enrichment factor when the insect moults [12], as we have shown for individual cockroaches from natural habitats, including those specifically associated with epiphytic bird's nest ferns in a rainforest canopy in Borneo (figure 2). Arthropods of this particular forest show a strong response to temperature and moisture gradients [5], which are a common feature of tropical forest canopies, often being associated with vertical stratification [2]. However, bird's nest ferns buffer microclimatic fluctuations [13], and provide discrete habitats for their invertebrate inhabitants [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of daily mean humidity is then transferred isotopically into the chitin (C 8 H 13 O 5 N), together with a systematic (and constant) enrichment factor when the insect moults [12], as we have shown for individual cockroaches from natural habitats, including those specifically associated with epiphytic bird's nest ferns in a rainforest canopy in Borneo (figure 2). Arthropods of this particular forest show a strong response to temperature and moisture gradients [5], which are a common feature of tropical forest canopies, often being associated with vertical stratification [2]. However, bird's nest ferns buffer microclimatic fluctuations [13], and provide discrete habitats for their invertebrate inhabitants [9].…”
Section: Discussionmentioning
confidence: 99%
“…Insects and other tracheated arthropods, which make up three-quarters of all animal species [4], show a strong response to moisture gradients in tropical forests [5]. These animals respire through a series of spiracles, the tracheal openings which allow air to diffuse into the animal while optimizing gas exchange and controlling respiratory water loss [6].…”
Section: Introductionmentioning
confidence: 99%
“…This represents a considerable proportion of arthropods found in the forest canopy as a whole. Based on previous work [19] in the same forest, which showed that 60.7 + 5.1% (n ¼ 6) of arthropods were found in the lower 16 m of the canopy, approximately 43 per cent of canopy arthropods could therefore be dependent on these networks.…”
Section: Discussionmentioning
confidence: 97%
“…For the bottom-up methods used in this analysis, an arthropod census must be taxonomically broad, use indiscriminate sampling methods designed to sample arthropods with different habitat preferences, and be drawn from a complete and clearly defined contiguous area. Of the arthropod censuses conducted in Borneo (Kitching et al 2001;Basset et al 2003;Beck et al 2006;Dial et al 2006;Beck and Rüdlinger 2014;Stork 2015, and references therein), we are not aware of any that meet these three criteria. The most comprehensive census of which we are aware that meets these criteria is a survey of lowland tropical forest in the San Lorenzo forest, Panama (Basset et al 2012).…”
Section: Census Datamentioning
confidence: 99%